Travelling Gestures - Elfriede Jelineks Theater der (Tragödien-)Durchquerung - Felber, Silke (mdwPress, 2023)
Silke Felber describes Jelinek's theater of (tragedy) traversal for the first time at the intersection of theater, literary, and cultural studies. In the form of a richly detailed study, this foundational work reveals gestures of lamentation and anger that extend back to antiquity while simultaneously pointing toward an uncertain future.